Sex differences in the ventilatory responses to exercise in mild to moderate obesity. Issue 8 (17th July 2022) - Bhammar, Dharini M.; Balmain, Bryce N.; Babb, Tony G.; Bernhardt, Vipa
Abstract : New Findings: What is the central question of the study? What are the sex differences in ventilatory responses during exercise in adults with obesity? What is the main finding and its importance? Tidal volume and expiratory flows are lower in females when compared with males at higher levels of ventilation despite small increases in end‐expiratory lung volumes. Since dyspnoea on exertion is a frequent complaint, particularly in females with obesity, careful attention should be paid to unpleasant respiratory symptoms and mechanical ventilatory constraints while prescribing exercise. Abstract: Obesity is associated with altered ventilatory responses, which may be exacerbated in females due to the functional consequences of sex‐related morphological differences in the respiratory system. This study examined sex differences in ventilatory responses during exercise in adults with obesity. Healthy adults with obesity ( n  = 73; 48 females) underwent pulmonary function testing, underwater weighing, magnetic resonance imaging (MRI), a graded exercise test to exhaustion, and two constant work rate exercise tests; one at a fixed work rate (60 W for females and 105 W for males) and one at a relative intensity (50% of peak oxygen uptake, V ̇ O 2 peak ${\dot{V}}_{{{\rm{O}}}_{\rm{2}}{\rm{peak}}}$ ). Metabolic, respiratory and perceptual responses were assessed during exercise. Compared with males, females used a smaller proportion of their ventilatory capacity at peak exercise (69.13 ± 14.49 vs. 77.41 ± 17.06% maximum voluntary ventilation, P  = 0.0374). Females also utilized a smaller proportion of their forced vital capacity (FVC) at peak exercise (tidal volume: 48.51 ± 9.29 vs. 54.12 ± 10.43%FVC, P  = 0.0218). End‐expiratory lung volumes were 2–4% higher in females compared with males during exercise ( P  < 0.05), while end‐inspiratory lung volumes were similar. Since the males were initiating inspiration from a lower lung volume, they experienced greater expiratory flow limitation during exercise. Ratings of perceived breathlessness during exercise were similar between females and males at comparable levels of ventilation. In summary, sex differences in the manifestations of obesity‐related mechanical ventilatory constraints were observed. Since dyspnoea on exertion is a common complaint in patients with obesity, particularly in females, exercise prescriptions should be tailored with the goal of minimizing unpleasant respiratory sensations.